2014
DOI: 10.1103/physrevd.90.094504
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of the charm quark in theΔI=1/2rule

Abstract: Abstract:We study the dependence on the charm quark mass of the leading-order lowenergy constants of the ∆S = 1 effective Hamiltonian, with the aim of elucidating the role of the charm mass scale in the ∆I = 1/2 rule for K → ππ decay. To that purpose, finite- techniques are used to obtain a signal for penguin contractions in correlation functions involving four-fermion operators. The important role played by the subtractions required to construct renormalised amplitudes for m c = m u is discussed in detail. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Our physics results are presented in a companion paper [21]; preliminary results from this study have also been reported in Ref. [22].…”
Section: Eye Diagrams For K → πmentioning
confidence: 89%
See 4 more Smart Citations
“…Our physics results are presented in a companion paper [21]; preliminary results from this study have also been reported in Ref. [22].…”
Section: Eye Diagrams For K → πmentioning
confidence: 89%
“…SVS will also be applied to propagators connecting four-fermion operators and interpolating meson operators, which are also connected to large statistical fluctuations. Physics applications are discussed in a companion paper [21]; preliminary results of our study were also presented in Ref. [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations